Rent-seeking for pure public goods: Wealth and group's size heterogeneity (2011)
In this paper, we study how between-group wealth and size heterogeneity affect aggregate rent-seeking efforts as well as success probabilities when two groups compete for the allocation of a pure public good. Unlike with previous analyses on between-group asymmetries, we measure the utility cost of rent-seeking in terms of the loss in private consumption an individual faces when contributing to this activity. This allows us to analyze both how asymmetries in either group¿s size or wealth affect aggregate rent-seeking efforts when group size is not neutral, and how the interaction between two dimension asymmetries affects aggregate rent-seeking efforts in this context. Our main general result is that fewer between-group asymmetries do not necessarily imply greater aggregate rent-seeking efforts. We describe the circumstances under which this happens. The result is at odds with the commonly held notion that the more homogeneous the contestants in a static rent-seeking model, the greater the aggregate rent-seeking efforts.